2023
DOI: 10.1302/0301-620x.105b10.bjj-2023-0030.r2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for blood transfusion and postoperative anaemia following total knee arthroplasty

David A. Kolin,
Peter K. Sculco,
Alejandro Gonzalez Della Valle
et al.

Abstract: AimsBlood transfusion and postoperative anaemia are complications of total knee arthroplasty (TKA) that are associated with substantial healthcare costs, morbidity, and mortality. There are few data from large datasets on the risk factors for these complications.MethodsWe retrospectively reviewed the records of TKA patients from a single tertiary care institution from February 2016 to December 2020. There were a total of 14,901 patients in this cohort with a mean age of 67.9 years (SD 9.2), and 5,575 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In Downey et al ., a retrospective analysis of local hip fracture cases from 36 different countries, the 1‐year mortality of patients was revealed as 2.4%–34.8% after a surgery for hip fractures 22 . Another study demonstrated that the 5‐year death rate was 21.1% in 221 patients (>70 years) with hip fractures who underwent selective surgery 13 . The postoperative 1, 3, and 5‐year death rates in our study are reliable and important findings.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In Downey et al ., a retrospective analysis of local hip fracture cases from 36 different countries, the 1‐year mortality of patients was revealed as 2.4%–34.8% after a surgery for hip fractures 22 . Another study demonstrated that the 5‐year death rate was 21.1% in 221 patients (>70 years) with hip fractures who underwent selective surgery 13 . The postoperative 1, 3, and 5‐year death rates in our study are reliable and important findings.…”
Section: Discussionsupporting
confidence: 70%
“…The following data for patients were collected by reviewing the medical record system: sex, age, body mass index (BMI), hospital stay, smoking history, drinking history, number of co‐morbidities, diabetes, hypertension, osteoporosis, fracture type (garden typing), preoperative nutritional risk score (NRS), and American Society of Anesthesiologists (ASA) score; operative manners (SHA and THA); anesthesia method (general anesthesia and lumbar anesthesia); operation time (> = 2h / joint); preoperative laboratory examination indicators, including white blood cell (WBC), red blood cell (RBC), hemoglobin (HB), hematocrit (HCT), percentage of neutrophils (NEUT%), C‐reactive protein (CRP), serum K + , blood urea nitrogen (BUN), creatinine (CR), albumin (ALB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), international normalized ratio (INR), activated partial thromboplastin time (APTT), fibrinogen (FIB), thrombin time (TT), and prothrombin time (PT); associated operation indicators, including bleeding volume; blood transfusion volume; and postoperative laboratory examination indicators, including RBC, HB, 12,13 ALB, 14,15 K + , 12,16 in agreement with many previous studies. Based on the follow‐up results, the postoperative survival time and death rates of patients were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these efforts include the correction of anemia prior to surgery, performing surgery under regional hypotensive anesthesia, and utilizing a tourniquet (ICM Philly, n.d.; Lu et al, n.d.). Furthermore, perioperative administration of tranexamic acid, endorsed by the ICM 2018, to all patients undergoing orthopedic procedures is yet another effective measure to reduce blood loss (ICM Philly, n.d.;Schmied et al, n.d.;Kolin et al 2023;Yazdi et al 2020). The administration of tranexamic acid needs to be weight-based and administered approximately 20 minutes prior to surgery.…”
Section: Step 6 Minimization Of Blood Lossmentioning
confidence: 99%